Here's the question you clicked on:
fauxshaux
How can I apply the product rule to products of more than two functions?
$$A \left( X \right) * B \left( X \right) *C \left( X \right)$$
$$B(x)*(A \prime(x) * C(x) + C \prime(x) * A(x)) + A(x) * C(x)*B \prime(x)$$
(PQ)' = PQ' + P'Q let Q = RS => Q' = RS' + R'S So (PRS)' = (PQ)' = PQ' + P'Q = P(RS' + R'S) + P'(RS) (PRS)' = PRS' + PR'S + P'RS This may then be extended to all multiples by taking the sum of the derivative of each function, with the terms multiplied by all non-differentiated terms eg: (ABCD)' = ABCD' + ABC'D + AB'CD + A'BCD
I heard this was the second asked question in Math. x'D